Enhanced Intestinal Permeability of Cefixime by Self-Emulsifying Drug Delivery System: In-Vitro and Ex-Vivo Characterization - Arshad Mahmood; Laraib Khan; Muhammad Ijaz; Imran Nazir; Mahrukh Naseem; Muhammad Azam Tahir; Muhammad Naeem Aamir; Masood Ur Rehman; Mulazim Hussain Asim (Molecules, 2023)
Background: Cefixime (CFX) belongs to a group of third-generation cephalosporin antibiotics with low water solubility and low intestinal permeability, which ultimately leads to significantly low bioavailability. Aim: This study aimed to increase solubility, improve drug release, and intestinal permeability of CFX by loading into SEDDS. Methods: Suitable excipients were selected based on drug solubility, percent transmittance, and emulsification efficiency. Pseudo-ternary phase diagram was fabricated for the identification of effective self-emulsification region. The best probably optimized formulations were further assessed for encumbered drug contents, emulsification time, cloud point measurement, robustness to dilution, mean droplet size, zeta potential, polydispersity index (PDI), and thermodynamic and chemical stability. Moreover, in vitro drug release studies and ex vivo permeation studies were carried out and apparent drug permeability Papp of different formulations was compared with the marketed brands of CFX. Results: Amongst the four tested SEDDS formulations, F-2 formulation exhibited the highest drug loading of 96.32%, emulsification time of 40.37 ± 3 s, mean droplet size of 19.01 ± 1.12 nm, and demonstrated improved long-term thermodynamic and chemical stability when stored at 4 °C. Release studies revealed a drug release of 97.32 ± 4.82% within 60 min in simulated gastric fluid. Similarly, 97.12 ± 5.02% release of CFX was observed in simulated intestinal fluid within 120 min; however, 85.13 ± 3.23% release of CFX was observed from the marketed product. Ex vivo permeation studies displayed a 2.7-fold increase apparent permeability compared to the marketed product in 5 h. Conclusion: Owing to the significantly improved drug solubility, in vitro release and better antibacterial activity, it can be assumed that CFX-loaded SEDDS might lead to an increased bioavailability and antibacterial activity, possibly leading to improved therapeutic effectiveness.